2016
DOI: 10.3171/2016.2.peds15693
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic suturectomy with postoperative helmet therapy in bilateral coronal craniosynostosis

Abstract: OBJECTIVE Historically, bilateral frontoorbital advancement (FOA) has been the keystone for treatment of turribrachycephaly caused by bilateral coronal synostosis. Early endoscopic suturectomy has become a popular technique for treatment of single-suture synostosis, with acceptable results and minimal perioperative morbidity. Boston Children's Hospital has adopted this method of treating early-presenting cases of bilateral coronal synostosis. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 29 publications
3
40
1
2
Order By: Relevance
“…36.3 months, which is similar to the mean follow-up of 36.8 months and 37 months reported by Han et al 8 and Rottgers et al, 20 respectively. Furthermore, Rottgers et al reported that in their series, secondary FOAs were performed an average of 15 months after endoscopic surgery, with the latest revision taking place 22.7 months after the endoscopic procedure.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…36.3 months, which is similar to the mean follow-up of 36.8 months and 37 months reported by Han et al 8 and Rottgers et al, 20 respectively. Furthermore, Rottgers et al reported that in their series, secondary FOAs were performed an average of 15 months after endoscopic surgery, with the latest revision taking place 22.7 months after the endoscopic procedure.…”
Section: Discussionsupporting
confidence: 86%
“…An additional 18 patients with bilateral coronal craniosynostosis treated endoscopically, 9 of whom were di- agnosed with syndromic craniosynostosis, were recently reported by Rottgers and colleagues. 20 The syndromes that were involved included Saethre-Chotzen (n = 3), Apert (n = 2), Muenke (n = 3), and Pfeiffer (n = 1). Although the authors did not analyze syndromic and nonsyndromic patients separately, the overall mean age at surgery was 2.6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a minimally invasive approach, especially endoscopic suturectomy, may be used in some cases to correct the positional deformities surgically. The remodeling helmets can be used for very young patients (i.e., younger than 6 months) alone or in combination with suturectomy [52][53][54].…”
Section: Treatment and Complicationsmentioning
confidence: 99%